2016
DOI: 10.1016/j.matbio.2016.01.013
|View full text |Cite
|
Sign up to set email alerts
|

Keloids: The paradigm of skin fibrosis — Pathomechanisms and treatment

Abstract: Keloids, fibroproliferative dermal tumors with effusive accumulation of extracellular matrix (ECM) components, particularly collagen, result from excessive expression of growth factors and cytokines. The etiology of keloids is unknown but they occur after dermal injury in genetically susceptible individuals, and they cause both physical and psychological distress for the affected individuals. Several treatment methods for keloids exist, including the combination therapy of surgical incision followed by intrale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
308
2
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 293 publications
(325 citation statements)
references
References 93 publications
9
308
2
6
Order By: Relevance
“…Interestingly, in line with observations about AM treatment inducing re‐epithelialization of chronic wounds (Alcaraz et al, ; Insausti, Alcaraz, et al, ), previous work in our laboratory has demonstrated that AM is able of attenuating the expression profile of relevant genes involved in cell cycle regulation under TGF‐ß control (Alcaraz et al, ), which resembles how attenuation of TGF‐ß signalling has also been demonstrated to be critical for some tumour cells to escape from cell cycle arrest (Nicolas & Hill, ). In that sense, exacerbated canonical TGF‐ß signalling has been linked to the promotion of skin fibrosis in an intricate process that involves fibroblast, keratinocyte and leucocyte interaction (Andrews, Marttala, Macarak, Rosenbloom, & Uitto, ; Ashcroft & Roberts, ). Coherently, interfering with TGF‐ß signalling by means of AM treatment may emerge as a good strategy for addressing skin fibrosis in humans.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, in line with observations about AM treatment inducing re‐epithelialization of chronic wounds (Alcaraz et al, ; Insausti, Alcaraz, et al, ), previous work in our laboratory has demonstrated that AM is able of attenuating the expression profile of relevant genes involved in cell cycle regulation under TGF‐ß control (Alcaraz et al, ), which resembles how attenuation of TGF‐ß signalling has also been demonstrated to be critical for some tumour cells to escape from cell cycle arrest (Nicolas & Hill, ). In that sense, exacerbated canonical TGF‐ß signalling has been linked to the promotion of skin fibrosis in an intricate process that involves fibroblast, keratinocyte and leucocyte interaction (Andrews, Marttala, Macarak, Rosenbloom, & Uitto, ; Ashcroft & Roberts, ). Coherently, interfering with TGF‐ß signalling by means of AM treatment may emerge as a good strategy for addressing skin fibrosis in humans.…”
Section: Discussionmentioning
confidence: 99%
“…Current skin fibrosis treatments typically require expensive pharmacologic, surgical, or invasive treatments associated with a significant risk of side effects. Even with combination therapy and a good treatment outcome, skin fibrosis frequently recurs .…”
Section: Introductionmentioning
confidence: 99%
“…Keloid is a fibrotic dermal tumor with overproduction of extracellular matrix components such as collagen, due to excessive expression of growth factors and cytokines . Significant upregulation of galectin‐1 in keloid tissue extract was reported by comparative proteomic analysis .…”
Section: Fibrotic Disordersmentioning
confidence: 99%